Congress and China policy past episodic, recent enduring influence - Sutter, Robert G. 1943- (Lexington Books, 2024)
"Filling major gaps in assessing Congress in US policy toward China, this book compares bipartisan Congressional majorities resolutely defending America from serious contemporary Chinese challenges with past episodes of Congressional activism. It shows the majorities exerting unprecedented influence, likely to continue during the tenure of this large Congressional cohort"--